Paediatric frequent use of emergency medical services: a systematic review. Issue 1 (6th December 2022) - Scott, Jason; Khanom, Ashrafunessa; Straw, Joanne; Strickland, Annette; Porter, Alison; Snooks, Helen
Abstract : Background: Frequent use of emergency medical services (EMS) is recognised to be a global phenomenon, although paediatric frequent use is poorly understood. This systematic review aimed to understand how paediatric frequent use of EMS is currently defined, identify factors associated with paediatric frequent use of EMS and determine effectiveness of interventions for paediatric patients who frequently use EMS. Methods: Four electronic databases (Medline, CINAHL, Web of Science and PsycINFO) were searched to September 2022 for primary, peer-reviewed research studies published in English from January 2000. Studies were included that examined frequent use (>1 contact during study period) of EMS or other services with arrival via EMS. Paediatric patients were defined as <18 years of age or otherwise defined by study authors as paediatric/adolescent/children. Data were extracted using a structured proforma, and quality was assessed using the Standard Quality Assessment Criteria for Quantitative Studies but did not influence inclusion decisions. Data were presented using narrative synthesis. Results: The search resulted in 4172 unique references, with 12 papers included in the review from 7 countries. Four were EMS studies, and eight Emergency Department with arrival via EMS. All studies used retrospective designs, with no interventional studies identified. Paediatric frequent EMS users were more likely to use services for medical reasons rather than trauma, including respiratory complaints, mental health and seizures, but data on gender and ethnicity were inconclusive and silent on socioeconomic status. There was no consistency in definitions of either a paediatric patient or of frequent use. Conclusion: The broad range of reasons for frequent use suggests that a single intervention is unlikely to be effective at addressing the causes of frequent use. There is a need for further research to better identify the underlying reasons for frequent EMS use among paediatric patients and to develop interventions in this population.